Indonesian EFL Students’ Thesis Writing in the Age of AI: Practices and Ethical Perspectives - Yustinus Calvin Gai Mali (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2026)
This study aims to explore how Indonesian EFL university students use Artificial Intelligence (AI) tools to support their undergraduate thesis writing, why they use those tools, and the AI-use policies they expect to have in their thesis writing process. To achieve these goals, the researcher conducted a qualitative case study involving five female EFL undergraduate students who were in the process of completing their theses at an English Education Program at a private university in Indonesia. Research data were collected through an in-depth semi-structured interview, supported by the students’ thesis draft to help them recall their thesis writing experiences. The researcher considered four rigor standards for qualitative studies: credibility, transferability, dependability, and confirmability to ensure the quality of the research findings. The inductive data analysis results revealed that students used four AI tools; ChatGPT, DeepL, Grammarly, and Quillbot in their thesis writing process to help them paraphrase, generate writing ideas, translate words and sentences, and select appropriate vocabulary. These tools were used because the students believed they might help enhance the quality of their writing, write faster, and increase their confidence in writing their thesis. At the same time, the students were also aware of the risks of being too dependent on AI tools and the inaccuracy of AI-generated texts and suggestions, which encouraged them to verify the AI outputs before incorporating them into their thesis. Practical implications for EFL lecturers who are supervising thesis students and directions for future research were presented.